ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL TURUNAN FUNGSI ALJABAR DITINJAU DARI KECERDASAN EMOSIONAL - Lepertery, Marselina Elizabeth; Ayal, Carolina Selfisina; Palinussa, Anderson Leonardo (Jurnal Pendidikan Matematika Unpatti, 2022)
This study aims to analyze and describe students difficulties in solving problems derived from algebraic functions in terms of emotional intelligence in class XI SMA Negeri 4 Central Maluku. This type of research is quantitative-qualitative research. The source of data in this study was students of class XI MIPA 3 SMA Negeri 4 Central Maluku with a total of 28 students, and the subjects in this study were 2 students including 1 student in the high emotional intelligence category, and 1 student representing the medium emotional intelligence category. The instruments used in this study were emotional intelligence questionnaires, algebraic function derivative test questions and interviews. The results showed that the difficulties experienced by students of class XI MIPA 3 SMA Negeri 4 Central Maluku in solving problems derived from algebraic functions include difficulties in understanding concepts, difficulties in understanding principles, and difficulties in operation. The results of the emotional intelligence questionnaire showed that the emotional intelligence of students of SMA Negeri 4 Central Maluku was in the high category. The results of the questionnaire averaged the percentage of emotional intelligence of students with high categories of 71.43%, emotional intelligence of students with moderate categories of 28.57%, and the average emotional intelligence of students with low categories of 0%, meaning that none of the students had low levels of emotional intelligence